Shift of Political Determination upon Law in Indonesia - Nasution, Krisnadi; Hadi, Syofyan (Opción, 2019)
During the Dutch Colonial Government until the end of the era of President Soeharto, law in Indonesia was a crystallization of political intentions interacting mutually and even competing each other, so that politics became determinant upon the law. Begins during reformation, the shift in political determination started to occur upon the law. Tidal of testing right to rules of law is significant influence to determinant upon the law. Since the establish- ment of Constitutional Court of the Republic of Indonesia in 2003, testing towards rules of law can be conducted below the law upon the law. Through the Testing Right to Rules of Law, the law becomes more determinant upon politics.